Mismatches in the urbanization process of informal settlements in Morro da Cruz - Florianopolis, SC - Soares,Sonia Rohling (2019)
Abstract Brazilian political-administrative structures often arise on institutional and legal mazes, reducing the effectiveness to solve the unsatisfactory living conditions in poor communities. Unraveling conflicts and finding alternative can contribute to better life quality and improved structures. This article discusses the lack of coherence among technical diagnoses, community demands, and actions of public administration in urban areas exposed to landslide risk, and studies the case of informal settlements of Morro da Cruz, in Florianópolis, southern Brazil. The susceptibility to landslides and the poor living conditions of about 40% of the population living there, led these communities to receive investments from the Growth Acceleration Program (PAC) of Brazil´s Federal Government which main interventions (2009-2016) should be the construction of social housing and land regularization for the inhabitants since the data showed in 2008 a deficit of 438 houses and had 80% of properties without due documentation. An evaluation in 2016 showed those interventions in Morro da Cruz improved living conditions, however, they did not complete land regularization, eliminate the housing deficit nor the susceptibility. In conclusion, we point out the main gaps in the process and the possible support for an improvement of the structures for such interventions in the Brazilian context.